Alguns aspectos da mortalidade entre japoneses e seus descendentes residentes no município de São Paulo, Brasil Some aspects of mortality in Japanese and their descendants in the city of S. Paulo, Brazil - Sabina Léa Davidson Gotlieb (Universidade de São Paulo, 1974)
São analisadas algumas características da mortalidade entre imigrantes japoneses e seus descendentes residentes no município de São Paulo, comparando-as com a população do Japão e geral do município de São Paulo. Os imigrantes japoneses e seus descendentes apresentam padrão de mortalidade de nível intermediário entre o do local de origem e o de destino, aproximando-se mais do nível de saúde do Japão. A mortalidade infantil entre os descendentes dos imigrantes, nascidos no município de São Paulo, é bem inferior à do município de São Paulo. O risco de morrer por lesões vasculares que afetam o sistema nervoso central é mais alto no Japão. Por outro lado, o risco de morrer por doenças cardíacas é muito mais alto no município de São Paulo. Os imigrantes japoneses apresentam-se num nível intermediário de mortalidade pelas causas acima referidas. Tal fato sugere atuação de fatores ambientais, levando os imigrantes a adquirirem padrão de mortalidade do local de destino. Some mortality characteristics of Japanese immigrants and their descendants living in the city of S. Paulo, Brazil, are analysed. Comparison between these characteristics and those among the populations of Japan and the city of S. Paulo has been made. The Japanese immigrants and their descendants have an intermediate pattern of mortality ranking between the pattern of Japan and the S. Paulo one, being closer to the former. The infant mortality rate among the Japanese born in S. Paulo is much lower than the S. Paulo rate. The death rate for vascular lesions affecting the Central Nervous System is higher in Japan. On the other hand, the death rate for diseases of the heart (except rheumatic heart disease) is much higher in S. Paulo. The association of a low death rate for diseases of the heart with a high death rate for vascular lesions affecting the Central Nervous System is observed. The Japanese immigrants tend to occupy an intermediate mortality level for both causes of death here mentioned. These results suggest that the environmental factors play an important role in the immigrants' pattern of mortality.